First record of pantanal cat, Leopardus colocolo braccatus, in Bolivia - Diaz Luque, José Antonio (2012)
The Pantanal cat, Leopardus colocolo braccatus, has been reported for grasslands and subtropical humid forests in Brazil, Uruguay, Paraguay and Argentina. Here we report a dead Pantanal cat in the Moxos savannahs of the Beni Department of Bolivia, representing the first record of this taxon for Bolivia. This record, in combination with a reassessment of two previous records of L. colocolo in the lowlands of Bolivia, extends the distribution range of this subspecies ca.1000 km WNW from the nearest known locality in Brazil.